A comparison of students' game experiences throughout the development of the Number Navigation Game - Bui, Phuong (fi=Turun yliopisto|en=University of Turku|, 2017)
This study aims at analyzing students’ game experiences playing four consecutive versions of the Number Navigation Game (NNG) throughout the course of three years 2014-2016 to understand more about students’ serious gaming experiences; at the same time providing comprehensive descriptions of the game’s features after each update in order to unravel the elements that aided the gaming experiences in the development of NNG. The study employs a mixed-methods design of quantitative and qualitative research. Game Experience Questionnaire about 8 core game experience dimensions were answered by students at secondary schools in Turku, Finland after playing 4 versions of NNG from 2014 to 2016; and 6 semi-structured interviews related to game experiences of students playing the last version of NNG were conducted. The study found that there were significant differences between the students’ game experiences in all core dimensions, and game experiences had been positively improved with the later versions of the game. It implied that the changes and integrated features had been proved greatly effective in providing meaningful experiences for players. However, the result also indicated that the game experience of flow had not been reached as the game had been viewed as too simple or not challenging enough, suggesting that there is an absence of challenging elements in both the game’s form and the mathematic content. The findings of this study also suggest game personalization features like the “city page” and surprise elements like the “pirate ship” had significantly enhanced players’ game experience.